2017
DOI: 10.1111/nmo.13174
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic vomiting syndrome is a prevalent and under‐recognized condition in the gastroenterology outpatient clinic

Abstract: Background: Cyclic vomiting syndrome (CVS) is a functional gastrointestinal disorder

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…18 Hence, awareness of FNVDs is paramount, particularly because they frequently are underrecognized despite accounting for more than 10% of adult outpatient gastroenterology cases. 9 Moreover, there are no randomized controlled trials evaluating therapeutic options for FNVDs in adults. 19 Our findings hopefully will stimulate increased awareness and research efforts for these debilitating conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Hence, awareness of FNVDs is paramount, particularly because they frequently are underrecognized despite accounting for more than 10% of adult outpatient gastroenterology cases. 9 Moreover, there are no randomized controlled trials evaluating therapeutic options for FNVDs in adults. 19 Our findings hopefully will stimulate increased awareness and research efforts for these debilitating conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Second, although well-recognized conditions such as irritable bowel syndrome and functional dyspepsia have documented associations with increasing psychological distress, somatization, poorer quality of life, overlapping functional gastrointestinal disorders, and greater health care utilization, 6,7 there is a general paucity of data regarding FNVDs. A few studies have evaluated some health-related parameters within FNVD subtypes, [8][9][10][11] but no study has concurrently overseen multiple health parameters among all FNVD subtypes while using a non-FNVD control group. Third, the association between cannabis use and repetitive hot water bathing behavior has not been established in FNVDs outside of CVS, such as in CNVS.…”
mentioning
confidence: 99%
“…Some studies have shown that CVS is more common in women, but there have been mixed results regarding gender predilection. [177][178][179][180] Abdominal pain is considered by some to be essential for CHS diagnosis, but pain is also reported by a substantial proportion of patients with CVS. 181 More significantly, CHS has been prominently linked to a pattern of hot bathing or showering to relieve symptoms.…”
Section: Epidemiology and Clinical Featuresmentioning
confidence: 99%
“…Most clinicians consider CVS in adults to be rare, but a recent report calculated a prevalence of 10.8% among outpatients in a specialty gastroenterology clinic, a rate that approaches that of gastroparesis, chronic constipation, and irritable bowel syndrome in tertiary outpatient cohorts. [3][4][5][6] However, another recent population-based survey estimated a lower prevalence of 2% of CVS in adults. 7 While these preliminary estimates are important, determining the actual prevalence of CVS in adults has fundamental implications for allocation of funding and future research.…”
Section: Introductionmentioning
confidence: 99%